Relationship between The Adsorption Capacity of Pesticides by Wood Residues and The Properties of Woods and Pesticides - Rodriguez-Cruz, Sonia; Andrades, Maria S.; Sanchez-Camazano, Maria; Sanchez-Martin, Maria J. (Environmental Science & Technology, 2007)
With the aim to explore the potential use of wood residues in technologies aimed at preventing the pollution of soil and water, we studied the adsorption of four non-ionic pesticides (linuron, alachlor, metalaxyl, and chlorpyrifos) and two ionic pesticides (dicamba and paraquat) with a Kow range of ?4.5 to 4.7 by nine types of wood with lignin content in the 18.2?26.9% range. The Freundlich Kf values were considered as indicators of the adsorption capacity. A statistical study was carried out using simple and multiple correlations to establish the degree to which the different parameters of the woods and of the pesticides were involved in adsorption. In the case of the non-ionic pesticides, positive and negative significant correlations were observed between Kf and the lignin (r = 0.73?0.83, p < 0.05?0.01), and soluble C contents of the woods (r = 0.66?0.84), p < 0.1?0.01). For dicamba, a correlation between Kf and pH (r = ?0.66, p < 0.1) of the woods was found, while for paraquat, this was seen between Kf and the cation exchange capacity (r = 0.71, p < 0.1) of the woods. No significant correlation was observed between Kf and the total C content of the woods. A highly significant correlation between Kf and Kow values (r ≥ 0.93, p < 0.01) was found in the adsorption of the pesticides by the woods (with the exception of paraquat) showing that this parameter is very important in this adsorption process. The determination coefficient of the multiple correlation between Kf and the parameters Kow, soluble C, and lignin contents accounts for nearly 100% of the variability in adsorption for non-ionic pesticides. Based on the results of our study and of those of the literature related to the adsorption of aromatic hydrocarbons, we used the Kow values to define a predictive model of adsorption of hydrophobic organic compounds in general by the woods.
doi: 10.1021/es062616fdoi: 10.1021/es062616fThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: lignin content; pesticide adsorption; wood properties (voyant); wood residues

Relationship between The Adsorption Capacity of Pesticides by Wood Residues and The Properties of Woods and Pesticides - Rodriguez-Cruz, Sonia; Andrades, Maria S; Sanchez-Camazano, Maria; Sanchez-Martin, Maria J (Environmental Science & Technology, 2007)
With the aim to explore the potential use of wood residues in technologies aimed at preventing the pollution of soil and water, we studied the adsorption of four non-ionic pesticides (linuron, alachlor, metalaxyl, and chlorpyrifos) and two ionic pesticides (dicamba and paraquat) with a Kow range of ?4.5 to 4.7 by nine types of wood with lignin content in the 18.2?26.9% range. The Freundlich Kf values were considered as indicators of the adsorption capacity. A statistical study was carried out using simple and multiple correlations to establish the degree to which the different parameters of the woods and of the pesticides were involved in adsorption. In the case of the non-ionic pesticides, positive and negative significant correlations were observed between Kf and the lignin (r = 0.73?0.83, p < 0.05?0.01), and soluble C contents of the woods (r = 0.66?0.84), p < 0.1?0.01). For dicamba, a correlation between Kf and pH (r = ?0.66, p < 0.1) of the woods was found, while for paraquat, this was seen between Kf and the cation exchange capacity (r = 0.71, p < 0.1) of the woods. No significant correlation was observed between Kf and the total C content of the woods. A highly significant correlation between Kf and Kow values (r ≥ 0.93, p < 0.01) was found in the adsorption of the pesticides by the woods (with the exception of paraquat) showing that this parameter is very important in this adsorption process. The determination coefficient of the multiple correlation between Kf and the parameters Kow, soluble C, and lignin contents accounts for nearly 100% of the variability in adsorption for non-ionic pesticides. Based on the results of our study and of those of the literature related to the adsorption of aromatic hydrocarbons, we used the Kow values to define a predictive model of adsorption of hydrophobic organic compounds in general by the woods.
doi: 10.1021/es062616f
Keywords: lignin content; pesticide adsorption; wood properties (voyant); wood residues

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.30110.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content